CROSS-CULTURAL ADAPTATION OF A TOOL TO ASSESS THERAPEUTIC EDUCATIONAL INTERVENTIONS FOR DIABETES PATIENTS - Laura Barbosa Nunes; Camila Aparecida Pinheiro Landim Almeida; Malvina Thaís Pachêco Rodrigues; Eliana Campêlo Lago; Luana Kelle Batista Moura; Magda Coeli Vitorino Sales Coêlho (Universidade Federal do Paraná, 2018)
Objective: to identify the use of contraceptive methods by adolescents of a public school in the state of Maranhão. Method: a quantitative, descriptive-exploratory, cross-sectional study was conducted between November and December 2015, with high school adolescents from a public school in the state of Maranhão. Descriptive statistical analysis of the data was performed. Results: of the adolescents, 199 (88.1%) reported having information on contraceptive methods, which was mainly obtained from their mothers, by 139 (69.8%). Of the young women who had information, 184 (92.5%) reported knowing about the male condom. Of the adolescents who had already started sexual activity, some reported not using any method, despite having the information, and 59 (76.6%) young women reported having used the male condom. Conclusion: there is a need to constantly develop health actions in order to allow adolescents to exercise their sexuality more safely, so they avoid sexually transmitted infections and unplanned pregnancies.